Transection of rat fimbria-fornix induces lasting expression of c-Jun protein in axotomized septal neurons immunonegative for choline acetyltransferase and nitric oxide synthase - Brecht, Stephan; Martín-Villalba, Ana; Zuschratter, Werner; Bravo, R.; Herdegen, Thomas (Experimental neurology, 1995)
The fimbria-fornix (FF) fiber tract was unilaterally transected in adult rats by a stereotaxic knife cut. In the axotomized neurons of the medial septal nucleus (MS) and ventral diagonal hand of Broca (VDB), the expression of Jun, Fos, Krox, CREB transcription factors, choline acetyltransferase (ChAT) and nitric oxide synthase (NOS) were studied by immunocytochemistry. In addition, NADPH-diaphorase (NDP) and acetylcholine esterase (AChE) were visualized by activity assays. For retrograde tracing of axotomized neurons, either HRP-coupled gold was injected in the entorhinal cortex prior to axotomy, or Fast Blue was injected into the transection site subsequently to FF transection. Following FF transection c-Jun and in a less extend JunD were expressed in axotomized MS and VDB neurons. Expression levels rose at 24 h, but not at 18 h, postaxotomy, reached their maximal levels between 5 and 7 days, and then gradually declined. Up to 100 days, c-Jun was still present in a substantial number of septal neurons. JunB, Krox-20, Krox-24, c-Fos, and pan-Fos immunoreactivities (IR) were not detectable in axotomized septal neurons and CREB-IR did not change compared to the intact contralateral side. ChAT-IR dramatically declined over 36 h, and furthermore AChE reactivity had substantially fallen after 5 days. The number and intensity of cytoplasmic neuronal NOS-IR and NDP which generated congruent temporospatial patterns gradually fell between 3 and 5 days postaxotomy. The surviving neurons labeled by NOS and NDP showed a high coexpression of c-Jun, whereas c-Jun was almost completely absent in neurons stained for ChAT and ACHE. Finally, ChAT-IR and NDP reaction labeled different subpopulations. Our findings demonstrate a lasting expression of the c-Jun transcription factor in axotomized MS and VDB neurons that might indicate the regenerative propensity of damaged neurons. The decrease of NOS and NDP in MS and VDB neurons demonstrates that neuronal populations respond to axotomy with an individual regulation of NOS expression.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 18.08.2025